CHRIMINALISTIC CHARACTERISTIC OF NEW WAYS OF COMMITTING CRIMES IN THE SPHERE OF CELLULAR COMUNICATION - D. S. Atov (Russian Journal of Economics and Law)
The article is devoted to criminological characteristics of ways of committing crimes in the area of cellular communication, as a "traditional" and appeared relatively recently, in 2008-2010. In this article, the author proposed the basic direction of counter such crimes.